Metabolic-BMI phenotypes as nutritional risk indicators for osteoarthritis: evidence from a prospective cohort of UK adults - Bao, Lei; Duan, Lincheng (Frontiers in Nutrition, 2025)
BackgroundMetabolic health status has emerged as a crucial nutritional and physiological indicator, reflecting the complex interplay between dietary intake, energy metabolism, and chronic disease risk. Obesity is a well-known risk factor for osteoarthritis (OA), yet substantial metabolic heterogeneity exists among individuals with obesity. Understanding how metabolic variability modifies the obesity-OA relationship can provide valuable insights into nutrition-related mechanisms of musculoskeletal health. This study aimed to examine the association between metabolic-BMI phenotypes and incident OA among middle-aged and older adults (MAOA) in the UK.MethodsThe ELSA provided the data. Metabolically healthy normal weight (MHNW), metabolically healthy overweight/obesity (MHOO), metabolically unhealthy normal weight (MUNW), as well as metabolically unhealthy overweight/obesity (MUOO) were the four metabolic-BMI phenotypes into which the participants were divided. The relationships between these phenotypes and incident OA were estimated via Cox proportional hazards models, which controlled for clinical variables, lifestyle choices, and sociodemographic traits.ResultsDuring a median follow-up of 10 years, 673 new OA cases were identified. Compared with the MHNW group, participants with MHOO (HR = 1.54, 95% CI: 1.19–2.01, p = 0.001) as well as MUOO (HR = 1.90, 95% CI: 1.46–2.47, p < 0.001) had significantly higher risks of developing OA, while no remarkable association was seen for the MUNW group (HR = 1.00, 95% CI: 0.68–1.46, p = 0.99). In the longitudinal analysis, individuals who remained in MUNW, MHOO, or MUOO categories—or transitioned from MHNW to MUOO, or from metabolically healthy to unhealthy states within the obese group—showed markedly increased risks of OA onset.ConclusionMetabolic status modified—but did not eliminate—the association between obesity and osteoarthritis risk. These findings highlight substantial heterogeneity within obesity phenotypes and suggest that incorporating metabolic health with BMI may improve identification of individuals at elevated OA risk.